A linex-ESTAR model of asymmetric government reactions to tourism demand - Pericleous, Katerina; Evangelides, Pavlos (My University, 2025)
To investigate asymmetric and nonlinear government responses to changes in tourism demand, a theoretical model is presented. Policymakers' greater aversion to perceived losses than to appreciation of comparable gains is reflected in the use of a Linex loss function to capture behavioral asymmetry. Dynamic regime-switching behavior is modeled using an Exponential Smooth Transition Autoregressive (ESTAR) specification, which permits both threshold-based and gradual policy changes. The model's structure is precisely defined to combine behavioral economics and demand analysis for tourism, providing a manageable and adaptable framework for simulation and empirical testing. When tourism is important, this strategy will alter how governments respond to unstable situations. By linking behavioural loss functions with nonlinear time series dynamics, the model gives applied econometric research in tourism and public policy a useful tool.
Keywords: Tourism demand; Policy asymmetry; Linex loss function; ESTAR model; Nonlinear dynamics; Government response